PENGARUH (EFEK) KEMOTERAPI TERHADAP KERJA (AKTIVITAS) ENZIM TRANSAMINASE DI PENDERITA KANKER PAYUDARA - Helena Leppong; Mutmainnah Mutmainnah; Uleng Bahrun (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Breast cancer is one of the malignancies with unknown exact aetiology. The management of breast cancer can be done by severalways including it’s related chemotherapy. This therapy leads to cancer cells damage as well as healthy liver cells. Aspartate transaminase(AST) and Alanine transaminase (ALT) are the sensitive parameters to evaluate hepatocellular damage, the levels will raise rapidly inliver cells injury. The objective of this study was to evaluate the effect of chemotherapy in the activity of liver transaminase enzymes ofbreast cancer patients. A cross-sectional study was conducted by taking data from Medical Records of breast cancer patients who receivedchemotherapy at the Dr. Wahidin Sudirohusodo Hospital Makassar during the period of May 2008–May 2009. The data were analyzedstatistically by t-Test using SPSS software for Windows version 11.5. From 71 evaluated samples, the level of the liver transaminaseenzymes in all grades of cancer did not show a significant change (p>0.05). Chemotherapy of breast cancer patients does not increasethe activity of transaminase enzymes. In this study, the level of AST and ALT in chemotherapy patients can not predict the liver functiondisorder.